2014
DOI: 10.1152/ajpendo.00559.2013
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of the Fibroblast growth factor 21 gene is an underlying cause of acinar cell injury in mice lacking MIST1

Abstract: Johnson CL, Mehmood R, Laing SW, Stepniak CV, Kharitonenkov A, Pin CL. Silencing of the Fibroblast growth factor 21 gene is an underlying cause of acinar cell injury in mice lacking MIST1. Am

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 55 publications
(81 reference statements)
1
27
1
Order By: Relevance
“…Our findings are consistent with reports showing that pancreatic FGF21 expression increases in mice with cerulein-induced pancreatitis [10, 11]. To our knowledge, only one other study has analyzed FGF21 levels in human acute pancreatitis [14].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are consistent with reports showing that pancreatic FGF21 expression increases in mice with cerulein-induced pancreatitis [10, 11]. To our knowledge, only one other study has analyzed FGF21 levels in human acute pancreatitis [14].…”
Section: Discussionsupporting
confidence: 93%
“…While FGF21 expression is highest in the pancreas[9], few studies have addressed the possible role of FGF21 in this tissue. In mice, increased pancreatic FGF21 is seen with cerulein-induced pancreatic injury, with more severe injury observed in mice lacking FGF21 [10, 11]. To assess the possibility that FGF21 is released from the pancreas during acute injury in humans, we measured circulating FGF21 in subjects with acute pancreatitis over the course of their disease.…”
Section: Introductionmentioning
confidence: 99%
“…Fgf21 -knockout (KO) mice have a heightened susceptibility to pancreatic inflammation and injury caused by the potent cholecystokinin (CCK) analog cerulein (Johnson et al, 2009). Likewise, mice lacking the pancreatic transcription factor MIST1 are susceptible to pancreatitis due to silencing of the Fgf21 gene (Johnson et al, 2014). Conversely, FGF21 overexpression protects the pancreas against inflammation and injury in both cerulein-treated and MIST1-knockout mice (Johnson et al, 2014; Johnson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, pancreatic inflammation and fibrosis were increased in Fgf21 K/K mice compared to control mice and, conversely, were decreased in Fgf21 transgenic mice (Johnson et al 2009). Furthermore, FGF21 expression was markedly reduced in acinar cells of Mist1 knockout mice showing early events of pancreatitis such as the premature activation of digestive enzymes and acinar disorganization (Johnson et al 2014). These results suggest that FGF21 induction may be an adaptive mechanism to protect the development and progression of pancreatitis.…”
Section: Fgf21 and Pancreatitismentioning
confidence: 79%
“…Several studies have shown that FGF21 modulates the development and progression of pancreatitis, a known risk factor for pancreatic cancer (Johnson et al 2009(Johnson et al , 2014. In mice with cerulein-induced acute pancreatitis, FGF21 expression was increased in acinar cells but not in islet cells.…”
Section: Fgf21 and Pancreatitismentioning
confidence: 99%